Histological progression and bacterial load dynamics of Renibacterium salmoninarum in Chinook salmon Oncorhynchus tshawytscha - Dils, Riley E; Firestone, Tawni B R; Schaffer, Paula A; Winkelman, Dana L; Fetherman, Eric R (Diseases of aquatic organisms, 2025)
Renibacterium salmoninarum, the cause of bacterial kidney disease (BKD), severely impacts salmonid populations. Much of our understanding of the BKD pathology in salmonids comes from evaluating fatal infections in wild populations or spawning Pacific Northwest salmonids. Our study investigated the histological progression and bacterial load dynamics of R. salmoninarum infection in Chinook salmon following intraperitoneal injection to enhance understanding of the disease's dynamics. Seventy presmolt salmon were injected with the ATCC-33209 isolate of R. salmoninarum and monitored over 10 wk. Histological signs of disease were observed in spleen and liver tissues at 1 wk post-injection and in kidney tissues at 4 wk post-injection, with signs of disease increasing over time. Additionally, histopathological analysis revealed splenic and hepatic capsulitis (coelomitis), individual hepatocyte necrosis, progressive granulomatous hepatitis, splenitis, and nephritis with necrosis. Gram staining confirmed the presence of Gram-positive bacteria within macrophages and extracellularly in infected tissues. Quantitative PCR revealed significant increases in bacterial loads in both kidney and liver tissues over the study period, with higher bacterial loads observed in the kidney tissue. Bacterial load was strongly correlated with disease stage, with peak bacterial burdens coinciding with the most severe histological changes. Our study provides a comprehensive account of R. salmoninarum infection and disease progression in Chinook salmon after intraperitoneal injection.